The Effect of Promotion Mix on Purchase Decisions at Fahira Hotel Bukittinggi - Putri, Liyan Andika; Pasaribu, Pasaribu (Institut Pariwisata dan Bisnis Internasional, 2022)
This research was motivated by the author when pre-research through observation and interviews with the general manager of Fahira Hotel Bukittinggi the author found problems such as unstable room occupancy rates, lack of effective promotion carried out, lack of trust from guests in hotel facilities. This study aims to analyze the effect of the promotion mix on purchasing decisions at Fahira Hotel Bukittinggi. By using a purposive sampling technique with the use of primary data in this study by distributing questionnaires and google forms. Then the research results were obtained, then the data was processed so that it could be stated that the promotion mix was in the bad category of 31%, the purchase decision was in the pretty good category with a regression coefficient of 0.431 and a sig. 0.000 ≤ 0.05. Furthermore, the obtained R square value of 0.186 means that the influence between the two variables is 18.6% and 81.4% influenced by other factors.